Pleiotropic effects of Metadoxil in the treatment of acute and chronic alcohol intoxications - Yu. V. Bykov; R. A. Bekker (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2023)
This article presents a review of modern scientific data concerning the safety and efficacy of the use of Metadoxil at different stages of the treatment of alcohol use disorder (from acute alcohol intoxication to the alcohol withdrawal syndrome, to the post-withdrawal period and remission stabilization), as well as a review of the advantages of Metadoxil use in such patients, due to the neuro- and hepatoprotective effects of this medication. Authors also describe a clinical case from their own practice. In the aforementioned case, the use of Metadoxil as a part of combination therapy contributed not only to the stabilization of remission of the alcohol use disorder, but also to diminishing of symptoms of comorbid mental (obsessive-compulsive disorder) and somatic (alcoholic fatty liver disease) diseases.